Application of Contextual Teaching and Learning Methods to Improve Students' Learning Outcomes - Adiwibowo, Prajayanto; Bahtiar, Yuyun (LPPM Universitas KH. A. Wahab Hasbullah, 2024)
Based on observations during teaching in class IV SDN Cikarang City 04, the learning outcomes of class IV students are still relatively low with an average score obtained of 59, the learning outcomes of class IV students are still relatively low because the learning process still uses a conventional approach and the lack of use of teaching aids. Contextual Teaching and Learning is a learning method that helps teachers relate the material they teach to situations in real life. The purpose of this learning improvement research is to improve the quality of learning carried out by teachers by applying the Contextual Teaching and Learning method to science learning in class IV SDN Cikarang City 04 as an effort to improve student learning outcomes. From the results of the research that has been conducted, the following conclusions can be obtained: the ability of teachers to teach by applying contextual methods is always developing and is already in the very good category in the final cycle. This can be seen from the average teacher activity of 44% in the fairly good category and in cycle I, it increased to 64% in the good category, and finally, in cycle II, it reached 84% in the very good category. From the results of this analysis, the contextual method can be used as an alternative in efforts to improve the learning outcomes of grade IV students of SDN Cikarang City 04 in the science subject.